THEME: THE IMPORTANCE OF IDENTIFYING TABOOS IN DIFFERENT CULTURES (Modern education and development, 2025)
Taboos are deeply ingrained cultural prohibitions that shape social interactions and behaviors. Understanding taboos across diverse cultures is critical for fostering cross-cultural communication, avoiding misunderstandings, and promoting social harmony. This study explores the significance of identifying taboos, using a qualitative approach to analyze their role in intercultural settings. Findings highlight that awareness of taboos enhances cultural sensitivity, reduces conflict, and supports effective global collaboration. Recommendations for integrating taboo awareness in education and professional training are discussed.